Shading-Dependent Greening Process of the Leaves in the Light-Sensitive Albino Tea Plant ‘Huangjinya’: Possible Involvement of the Light-Harvesting Complex II Subunit of Photosystem II in the Phenotypic Characteristic - Wang, Ying-Qi; Ye, Jing-Jing; Yang, Hong-Zhiyuan; Li, Da; Li, Xiao-Xiang; Wang, Yong-Kang; Zheng, Xin-Qiang; Ye, Jian-Hui; Li, Qing-Sheng; Liang, Yue-Rong; Lu, Jian-Liang (International journal of molecular sciences, 2023)
The light-sensitive albino tea plant can produce pale-yellow shoots with high levels of amino acids which are suitable to process high-quality tea. In order to understand the mechanism of the albino phenotype formation, the changes in the physio-chemical characteristics, chloroplast ultrastructure, chlorophyll-binding proteins, and the relevant gene expression were comprehensively investigated in the leaves of the light-sensitive albino cultivar ‘Huangjinya’ (‘HJY’) during short-term shading treatment. In the content of photosynthetic pigments, the ultrastructure of the chloroplast, and parameters of the photosynthesis in the leaves of ‘HJY’ could be gradually normalized along with the extension of the shading time, resulting in the leaf color transformed from pale yellow to green. BN-PAGE and SDS-PAGE revealed that function restoration of the photosynthetic apparatus was attributed to the proper formation of the pigment-protein complexes on the thylakoid membrane that benefited from the increased levels of the LHCII subunits in the shaded leaves of ‘HJY’, indicating the low level of LHCII subunits, especially the lack of the Lhcb1 might be responsible for the albino phenotype of the ‘HJY’ under natural light condition. The deficiency of the Lhcb1 was mainly subject to the strongly suppressed expression of the Lhcb1.x which might be modulated by the chloroplast retrograde signaling pathway GUN1 (GENOMES UNCOUPLED 1)-PTM (PHD type transcription factor with transmembrane domains)-ABI4 (ABSCISIC ACID INSENSITIVE 4).